Moral Reasoning at Work : Rethinking Ethics in Organizations - Kvalnes, Øyvind (Cham Springer Nature, 2019)
This book is open access under a CC-BY license. Moral dilemmas are a pervasive feature of working life. Moral Reasoning at Work offers a fresh perspective on how to live with them using ethics and moral psychology research. It argues that decision-makers must go beyond compliance and traditional approaches to ethics to prepare for moral dilemmas. The second edition has been updated with a range of examples from the author s more recent research, to reflect current issues affecting organizations in the digital age. With two new chapters on artificial intelligence and social media, this new edition provides an up-to-date overview of ethical challenges in organizations.
English
Keywords: Business strategy; Business ethics & social responsibility; Personnel & human resources management; Research & development management; Sales & marketing; Organizational theory & behaviour; Business; Management science; Business ethics; Personnel management; Organization; Planning; Leadership; Management; Industrial management; Internet marketing